2005
DOI: 10.1128/jcm.43.1.19-24.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Chlamydia pneumoniae in Atherosclerosis: More Evidence for Lack of Evidence

Abstract: During the past 15 years, many studies have been devoted to the relationship of Chlamydia pneumoniae and atherosclerosis: the serologic link has been investigated, and chlamydial organisms have been detected in lesions by electron microscopy, immunohistochemistry, in vitro cultivation, PCR, or in situ hybridization; efforts have been made to produce atherosclerosis experimentally in animals by inoculation of C. pneumoniae and therapeutic trials in humans have been undertaken. Some studies conclude that C. pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
3
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 78 publications
0
66
3
4
Order By: Relevance
“…The role of C. pneumoniae infection in the pathogenesis of atherosclerosis remains controversial (21)(22)(23)(24). Meta-analyses of randomized clinical trials of antibiotic therapy for secondary prevention of coronary heart disease did not show any benefit (25, 26).…”
Section: Pneumonia Infection and Atherogenesismentioning
confidence: 99%
“…The role of C. pneumoniae infection in the pathogenesis of atherosclerosis remains controversial (21)(22)(23)(24). Meta-analyses of randomized clinical trials of antibiotic therapy for secondary prevention of coronary heart disease did not show any benefit (25, 26).…”
Section: Pneumonia Infection and Atherogenesismentioning
confidence: 99%
“…Este es un valor elevado si se lo compara con estudios revisados en los últimos 5 años (15,(22)(23)(24)(25)(26). No obstante, en un estudio reciente, Bahrmand et al (6) demostraron que 12 de 14 (86%) casos eran positivos para C. pneumoniae por PCR en pacientes de 60 años o mayores.…”
Section: Discussionunclassified
“…La evidencia de una relación entre Chlamydia pneumoniae y la enfermedad coronaria es mucho más concluyente que para cualquier otro de los microorganismos posiblemente implicados (2,6,7,14), y se ha asociado con la presencia de enfermedad coronaria, carotídea, aneurismas de aorta y enfermedad vascular periférica (7). No obstante, otros reportes no confirman dicha asociación (15).…”
unclassified
See 1 more Smart Citation
“…Current studies indicate that this organism may also induce chronic inflammatory diseases such as asthma, arthritis, endocarditis and atherosclerosis [4][5][6][7]. Although accumulating studies have indicated a possible link between C. pneumoniae infection and chronic inflammatory diseases, the bacterial mechanisms involved in disease development remain unclear [8]. In addition to macrophages, lymphocytes are the major immune cell associated with the development of chronic inflammatory diseases, such as atherosclerosis [9,10].…”
Section: Introductionmentioning
confidence: 99%